Al-Imam Muhammad ibn Al-Hussein Al-Borjolani and his scientific life - Michael, Farag Salome; Khalaf, Najm Abdul Rahman; Al Nathar, Mohamed Khair Al-Nezam Zain (Journal of Humanities & Social Sciences, 2018)
A good volume of works, documentation and narration made by scholars through the history of the Ummah has been lost. In many cases, this is exacerbated by fewer attentions being paid to these narrations and biographies. In line with these facts, the current research explores one of the greatest Muslim scholars who contributed greatly to the Islamic science while considerable part of his production and narrations has unfortunately gone missing. This problem was a good reason for the researchers to engage in the current research, which is entitled “Al-Imam Muhammad ibn Al-Hussein Al-Borjolani and his scientific life”, in order to study and trace back his life using both deductive and synthetic approaches. While the main problem of this research focuses on the scientific life of Al-Imam Al-Borjolani and whether or not he significantly contributed to its enrichment, the aim is, however, to introduce him to readers and bring to light his scientific heritage, his students, teachers as well as the sayings, opinions and judgments of Muslim scholars about him. The study was divided into introduction and conclusion as well as two other chapters. One chapter was dedicated to the biography of the Imam and part of his scientific life, whereas the other chapter focused mainly on his teachers. The conclusion final conclusion encompassed reporting of the main findings including particularly that Al-Imam Muhammad ibn Al-Hussen al-Borjolani authored many books which were all lost except one book. Some of his books were not even mentioned in the known Muslim books of history and biographies. The research also concludes that this Imam is a trustable scholar. He narrated from over two hundred and seventy other Imams; out of which one hundred and eighty are also trustable Muslim scholars.